2020
DOI: 10.3390/foods9060697
|View full text |Cite
|
Sign up to set email alerts
|

Common Plant-Derived Terpenoids Present Increased Anti-Biofilm Potential against Staphylococcus Bacteria Compared to a Quaternary Ammonium Biocide

Abstract: The antimicrobial actions of three common plant-derived terpenoids (i.e., carvacrol, thymol and eugenol) were compared to those of a typical quaternary ammonium biocide (i.e., benzalkonium chloride; BAC), against both planktonic and biofilm cells of two widespread Staphylococcus species (i.e., S. aureus and S. epidermidis). The minimum inhibitory and bactericidal concentrations (MICs, MBCs) of each compound against the planktonic cells of each species were initially determined, together with their minimum biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Thymol has shown the ability to inhibit biofilm formation and eliminate the mature MRSA biofilm by inhibiting the synthesis of important biofilm components of these bacteria, such as polysaccharide intercellular adhesin (PIA) and extracellular DNA (eDNA), which is an important mechanism for S. aureus biofilm formation. These structures are responsible for, among other functions, supporting cell aggregation and adhesion to neutral solid surfaces, which determines antibiotic resistance [ 39 , 40 ]. Neither thymol nor vancomycin applied to MRSA colonies in the biofilm at the concentrations used showed complete bacterial elimination; however, in the combination of these compounds, the percentage of live bacteria was significantly reduced ( Figure 4 ), which suggests that thymol is effective in supporting the therapeutic effect of vancomycin on MRSA biofilms.…”
Section: Activity Against Microbiological Biofilmsmentioning
confidence: 99%
“…Thymol has shown the ability to inhibit biofilm formation and eliminate the mature MRSA biofilm by inhibiting the synthesis of important biofilm components of these bacteria, such as polysaccharide intercellular adhesin (PIA) and extracellular DNA (eDNA), which is an important mechanism for S. aureus biofilm formation. These structures are responsible for, among other functions, supporting cell aggregation and adhesion to neutral solid surfaces, which determines antibiotic resistance [ 39 , 40 ]. Neither thymol nor vancomycin applied to MRSA colonies in the biofilm at the concentrations used showed complete bacterial elimination; however, in the combination of these compounds, the percentage of live bacteria was significantly reduced ( Figure 4 ), which suggests that thymol is effective in supporting the therapeutic effect of vancomycin on MRSA biofilms.…”
Section: Activity Against Microbiological Biofilmsmentioning
confidence: 99%
“…This is still not always the case for many other pathogenic bacteria being enclosed in biofilm structures. For instance, in a previous related study, the application of BAC at 200 ppm caused only a 1.5 log reduction of an Staphylococcus aureus biofilm population (> 10 7 CFU/cm 2 ) on polystyrene surfaces [ 26 ]. Another aspect, however, that should be always also considered is the potential for bacterial cells surviving disinfection to enter the viable but not-culturable (VBNC) state, being thus unable to be enumerated by traditional plating methods, such as those here applied.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium, killing much more quickly the enclosed bacteria, compared to BAC [ 25 ]. In another recent study, evaluating and comparing the disinfection efficiency of THY and BAC against preformed biofilms of either S. aureus or Staphylococcus epidermidis , it was again shown that the phytochemical presented a significant lower resistance coefficient (Rc) than the synthetic biocide, meaning that the required increase in its concentration to be equally effective against biofilm cells as this was against the planktonic ones was much lower compared to the synthetic biocide [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations